Strategic management of digital transformation in Rural Banks: Evidence from Depok City in the open banking era - Prihatina Jati; Meirna Milisani; Ahmad Firdaus (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to analyze the effects of technology infrastructure, security and regulatory compliance, and human resource readiness on the collaboration of Rural Banks (BPR) with fintech and the open banking ecosystem, with digital service adoption as a moderating variable. Research Methodology: This research applied an associative quantitative method with a survey approach. Data were collected from 44 respondents representing 23 BPRs in Depok City. Respondents included executive officers, IT staff, and board members. The instrument used was a questionnaire distributed via Google Forms, and data analysis was performed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. Results: The findings show that human resource readiness has a significant positive effect on BPR–fintech collaboration. Technology infrastructure as well as security and regulatory compliance demonstrate no significant influence. Digital service adoption shows a positive but non-significant effect, although it moderates the negative influence of technology infrastructure. The research model obtained an R² value of 0.601, indicating a moderate explanatory power. Conclusions: The study concludes that human resources are the most critical determinant of successful BPR digital transformation and collaboration with fintech. Technical and regulatory factors contribute positively but insignificantly, while digital service adoption primarily plays a moderating role. Limitations: This study is limited to BPRs in Depok City with a relatively small sample size. Thus, the findings may not be generalizable to other regions or banking institutions. Contribution: This study contributes to the literature on financial digitalization by highlighting the central role of human resource readiness in fintech collaboration. Practically, it offers insights for BPR management, regulators, and policymakers in designing strategies to strengthen HR competence and digital adoption in the context of open banking.